PENGARUH HAND MASSAGE TERHADAP TINGKAT KECEMASAN PASIEN PRE-OPERASI SECTIO CAESARIA DI RSUD KEMBANGAN TAHUN 2024 - Trixy Mahalia; Yeni Koto; Susaldi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Childbirth via the caesarean section (SC) method is a complex event that is stressful and causes anxiety. Anxiety in mothers before caesarean section surgery, if not handled properly, will have a negative impact on the mother and the baby being born. The aim of this study was to determine the effect of hand massage on anxiety levels in preoperative Sectio Caesaria patients at Kembangan Regional Hospital. This research method is quantitative research that uses a pre-experimental method with a one group pre-test and post-test approach. This research involved 18 respondents using purposive sampling technique. The instrument used was an anxiety questionnaire from the Zung Self-rating Anxiety Scale (ZSAS) which consisted of 20 statements. The results of the study showed that the level of anxiety before being given the handmassage intervention was moderate anxiety (61.11%) and after being given the handmassage intervention it became mild anxiety (72.22%). The results of the Paired sample t-test obtained a p-value of 0.000 (α = 0.05), so it can be concluded that there is a significant effect of providing hand massage intervention on the anxiety level of pre-cesarean section patients. Suggestions from the results of this research are that it is hoped that nurses can provide independent intervention to reduce the anxiety level of patients before caesarean section surgery by providing hand massage interventions so that patients can undergo surgery in peace.